2012
DOI: 10.4314/ijbcs.v6i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Variation in biological parameters of cypermethrin resistant and susceptible strains of <em>Helicoverpa armigera</em> from Benin Republic, West Africa

Abstract: The aim of this survey was to assess the costs of cypermethrin resistance in Helicoverpa armigera strains by using variation in their biological parameters such as fecundity, number of larval slough, development time, weight and survival at each stage of insect development in comparison with susceptible strains. AGB01 and AGB03 are the resistant strains compared respectively with BK77 and OKP01 as susceptible strains. Fecundity, fertility and survival from egg to adult emergence of AGB03 strain were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
6
0
3
Order By: Relevance
“…La pleine dose de cyperméthrine appliquée durant plusieurs années en Afrique de l'Ouest et du Centre en général et au Bénin en particulier a entraîné l'apparition de la résistance de H. armigera aux pyréthrinoïdes dans ces régions (Martin et al, 2005 ;Djihinto et al, 2009Djihinto et al, et 2012Achaleke et Brévault, 2010). La lutte raisonnée expérimentée en culture cotonnière au Bénin à l'instar de la lutte étagée ciblée, la lutte sur seuil, la lutte après observation individuelle des chenilles appliquées en Afrique de l'Ouest et du Centre visant à réduire la dose d'insecticide épandu (Silvie et Sognigbe, 1993;Vodounnon, 1995;Nibouche et al, 2003;Sinzogan et al, 2004;Prudent et al, 2007;Silvie et al, 2011Silvie et al, et 2013Kpadé et Mensah, 2013;Brévault et al, 2014 ) est une stratégie de réduction de la pression de sélection insecticide et un outil de prévention et de gestion de la résistance des insectes aux insecticides (Djihinto, 2004;Djihinto et al, 2009Djihinto et al, et 2013.…”
Section: Discussionunclassified
“…La pleine dose de cyperméthrine appliquée durant plusieurs années en Afrique de l'Ouest et du Centre en général et au Bénin en particulier a entraîné l'apparition de la résistance de H. armigera aux pyréthrinoïdes dans ces régions (Martin et al, 2005 ;Djihinto et al, 2009Djihinto et al, et 2012Achaleke et Brévault, 2010). La lutte raisonnée expérimentée en culture cotonnière au Bénin à l'instar de la lutte étagée ciblée, la lutte sur seuil, la lutte après observation individuelle des chenilles appliquées en Afrique de l'Ouest et du Centre visant à réduire la dose d'insecticide épandu (Silvie et Sognigbe, 1993;Vodounnon, 1995;Nibouche et al, 2003;Sinzogan et al, 2004;Prudent et al, 2007;Silvie et al, 2011Silvie et al, et 2013Kpadé et Mensah, 2013;Brévault et al, 2014 ) est une stratégie de réduction de la pression de sélection insecticide et un outil de prévention et de gestion de la résistance des insectes aux insecticides (Djihinto, 2004;Djihinto et al, 2009Djihinto et al, et 2013.…”
Section: Discussionunclassified
“…Pyrethroid and organophosphate insecticides have been widely used by both cotton and tomato growers on account of their efficacy in controlling a wide range of pests at low doses and at extremely low cost (Badiane et al, 2015). As a result, resistance to pyrethroids occurred during the mid-1990s in H. armigera populations from West Africa (Martin et al, 2000;Djihinto et al, 2012). Resistance led to the wide adoption of a new spraying program based on the temporary exclusion of pyrethroids (Martin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that H. armigera has high movement and productiveness and it also revealed a great capability to develop resistance to insecticides used for its control (Ramasubramaniam and Regupathy, 2004). The cosmopolitan and polyphagous nature of the insect makes it have a wide host range and geographical distribution with the ability to adapt to new environments (Djihinto, 2012). H. armigera was reported to possess the ability to migrate from one fruit to the other without fully consuming it; and this explains the widespread damage of the insect to crops even when the larvae population is low (Zalucki et al, 1986).…”
Section: Introductionmentioning
confidence: 99%